University students’ Machiavellianism and self-monitoring on facebook: Mediating role of ethical positions - Ashraf, S. A.; Wu, Shin Ling *; Ong, Fon Sim; Chandrasekaran, V. (Springer, 2020)
This study examined the relationship between Machiavellianism and self-monitoring on Facebook. In addition, the mediating influence of ethical positions, i.e. relativism and idealism, on the relationship between Machiavellianism and self-monitoring on Facebook was tested. A cross-sectional study conducted on university students yielded 276 responses of Facebook users, which covered demographic characteristics, self-monitoring on Facebook, Machiavellianism, relativism and idealism. The results showed that Machiavellianism had a significant relationship with self-monitoring. When testing the mediating influence of relativism and idealism, it was found that relativism and idealism mediated the relationship between Machiavellianism and self-monitoring on Facebook where relativism was found to be a stronger mediator compared to idealism. Limitations of the study and suggestions for future research are presented.